Reduced M3 muscarinic acetylcholine receptor expression in gestational diabetes mellitus: implications for placental dysfunction and vascular regulation - Süleyman Cemil Oğlak; Fırat Aşır; Tuğcan Korak; Ayşegül Aşır; Emine Zeynep Yılmaz; Elif Ağaçayak (The Journal of Maternal-Fetal & Neonatal Medicine)
Objectives Gestational diabetes mellitus (GDM) is a prevalent metabolic disorder affecting pregnancy, leading to significant maternal and fetal complications. This study investigates the expression of M3 muscarinic acetylcholine receptor (mAChR) in GDM placentas and its potential implications for placental function.Methods A case–control study was conducted on placental samples from 40 GDM and 40 healthy pregnancies. Immunohistochemical (IHC) analysis was performed to evaluate M3 mAChR expression, and semi-quantitative assessments were conducted using ImageJ software. Placental samples of patients were tested with an ELISA kit. In-silico functional annotation analysis, including protein-protein interaction and KEGG pathway analysis, was utilized to explore the biological pathways associated with M3 mAChR dysregulation in GDM.Results Histopathological examination revealed significant structural alterations in GDM placentas, including increased fibrin deposition, syncytial knots, vascular congestion, and cellular degeneration. IHC analysis and tissue homogenate ELISA measurement demonstrated a significant reduction in M3 mAChR expression in GDM placentas compared to controls (p < 0.0001). KEGG pathway analysis of shared M3 mAChR and GDM protein targets revealed significant enrichment in endocrine, metabolic, vascular, cardiac, and neuroactive signaling pathways, suggesting their involvement in M3 mAChR-associated GDM mechanisms (false discovery rate [FDR] < 0.05).Conclusion The findings suggest that reduced M3 mAChR expression in GDM placentas may contribute to impaired cholinergic signaling, vascular dysfunction, and placental insufficiency. These alterations may play a role in the adverse pregnancy outcomes associated with GDM.